Framing Analysis from a Pedagogical Perspective – towards Media Education - Rzyska, Aleksandra (Przegląd Badań Edukacyjnych (Educational Studies Review), 2018)
The aim of the article is to show the educational potential of the framing analysis as an analytical proposal for pedagogical research. The research on framing focuses in a specific way on the analysis of the so called “frames”, i.e. the interpretative schemes included in media discourses. The possibilities of using the framing analysis in pedagogical research are presented as related to educational discourse as an object of pedagogical interest. The educational dimension of this kind of research is reconstructed by comparing and showing the relations of the current need for intervention in the field of media education and the need to involve discourse in research. In this way, the path from pedagogical research on framing to media education aimed at understanding and (re)constructing the meanings included in media messages has been outlined.